Analysis of photovoltaic systems with south and east-west photovoltaic panel azimuths - Keseev Ventsislav (E3S Web of Conferences)
The Photovoltaic (PV) systems are one of the key renewable energy technologies, but they have many drawbacks, which require their optimization. Certain private PV power plants in Bulgaria started to install their PV panels with East and West azimuths, instead of with the most power generating Southern orientation. PV systems with panels with South and East-West azimuths are compared. The analysis includes installation space, power generation for different days of the year in relation to daily energy price changes. The conclusion is that the most energy producing South azimuth may not be the optimal case when too many PV powers are installed as a percentage of the total grid power, which leads to wider daily energy price spreads and close to zero energy prices at noon. When all factors are taken under consideration, the East-West Azimut PV system with optimal Winter tilt offers even daily energy generation and the potential to outperform all other systems because it may require smaller and less expensive compensating energy storage systems, lower losses, it should improve the PV system lifetime due to the lower power load, and all of this in addition to the lower required installation space for certain required power.